Indications and clinical outcomes of fully covered self-expandable metallic tracheobronchial stents in patients with malignant airway diseases. (1st November 2020) - Akram, Muhammad Junaid; Khalid, Usman; Abu Bakar, Muhammad; Ashraf, Mohammad Bilal; Butt, Faheem Mehmood; Khan, Faheem
ABSTRACT: Background: Airway stenting is an efficacious approach in management of malignant airway disease (MAD) with improvement in survival outcome. Objective: To determine the indications and long-term clinical outcomes of tracheobronchial stenting in patients with MAD. Methods: A cross-sectional review of 51 patients who underwent airway stenting from June 2011 to June 2019 was done. Paired t-test was used to compare mean difference of clinical characteristics between pre- and post-airway stenting. Kaplan–Meier curves were used to assess overall survival. Results: A total of 51 patients had stent insertion with mean age 46.63±17.10years including 27(52.9%) females. Mainly 37(72.5%) patients had esophageal and 06(11.8%) had lung cancer. The main indications were bronchial stenosis 18(35.3%), tracheal stenosis 11(21.6%) and Tracheo-esophageal/bronchial fistula 13(25.5%). Obstruction was intrinsic, extrinsic and mixed in 20(39.2%), 13(25.5%) and 5(9.8%) patients, respectively. There was statistically significant mean difference in pre- and post-procedure oxygen saturation (mean (M)=89.8, standard deviation (SD)=6.70 vs M =95.5, SD=2.54.p =0.001) and performance status (M =3.65, SD =0.6 vs M =2.59, SD=0.83.p =0.001). Overall median survival was 16±3.44 weeks, highest amongst patients with intrinsic obstruction (27±6.51 weeks). Conclusion: Airway stenting is an effective endoscopic procedure to re-establish airway patency in MAD with minimal complications..